Development of a Geant4 application to characterise a prototype neutron detector based on three orthogonal 3He tubes inside an HDPE sphere. (January 2017) - Gracanin, V.; Guatelli, S.; Prokopovich, D.; Rosenfeld, A.B.; Berry, A.
Highlights: Geant4 study of a neutron detector with three 3 He orthogonal tubes inside a HDPE sphere. Geant4 physics models are adequate to characterise this detector. Result: The 3 He tube efficiency changes significantly with respect to position along the tube length. Indications on how to further investigate and asses the suitability of this detector. Abstract: The Bonner Sphere Spectrometer (BSS) system is a well-established technique for neutron dosimetry that involves detection of thermal neutrons within a range of hydrogenous moderators. BSS detectors are often used to perform neutron field surveys in order to determine the ambient dose equivalent H*(10) and estimate health risk to personnel. There is a potential limitation of existing neutron survey techniques, since some detectors do not consider the direction of the neutron field, which can result in overly conservative estimates of dose in neutron fields. This paper shows the development of a Geant4 simulation application to characterise a prototype neutron detector based on three orthogonal 3 He tubes inside a single HDPE sphere built at the Australian Nuclear Science and Technology Organisation (ANSTO). The Geant4 simulation has been validated with respect to experimental measurements performed with an Am-Be source.